2017
DOI: 10.3389/fimmu.2017.00523
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Reprogram IL-4/GM-CSF-Induced Monocyte Differentiation to Anti-inflammatory Macrophages

Abstract: Monocyte-derived dendritic cells (mo-DCs) are essential for the development of a Th1 protective immune response against Leishmania parasites. It is well known that IL-4 and GM-CSF drive differentiation of human monocytes to dendritic cells (DCs). Here, we investigate if neutrophil extracellular traps (NETs) disrupt this process. NETs-enriched supernatants, generated after human neutrophil activation by Leishmania promastigotes, were added to monocytes and differentiation monitored by expression of molecules as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Neutrophil extracellular traps and TLR7/8/9 have been linked to secondary self-NET propagation and have been shown to augment circulating levels of pro-inflammatory cytokines IL-10 and tumor necrosis factor-α (TNFα). 32,58 In our rat model of hind limb tourniquet-induced IR injury, 59,60 we show that IL-10 levels were significantly elevated at 6 and 24 hours post injury from 758 ± 244 pg/mL in uninjured animals to 1753 ± 121 pg/ mL at 6 hours (P < .0001) and 1659 ± 213 pg/mL at 24 hours (P < .0001) (Figure 2A). We found similar elevations in TNFα at 6 and 24 hours post injury from 2633 ± 1062 pg/mL to 7047 ± 1202 pg/mL (P < .0001) and 6717 ± 1183 pg/mL (P < .0001), respectively (Figure 2A), suggesting that IR injury mimicked other NET-related disease cytokine release, and similar TLR7/8/9 mediated pathways may have also been involved.…”
Section: Tnfα Productionmentioning
confidence: 69%
“…Neutrophil extracellular traps and TLR7/8/9 have been linked to secondary self-NET propagation and have been shown to augment circulating levels of pro-inflammatory cytokines IL-10 and tumor necrosis factor-α (TNFα). 32,58 In our rat model of hind limb tourniquet-induced IR injury, 59,60 we show that IL-10 levels were significantly elevated at 6 and 24 hours post injury from 758 ± 244 pg/mL in uninjured animals to 1753 ± 121 pg/ mL at 6 hours (P < .0001) and 1659 ± 213 pg/mL at 24 hours (P < .0001) (Figure 2A). We found similar elevations in TNFα at 6 and 24 hours post injury from 2633 ± 1062 pg/mL to 7047 ± 1202 pg/mL (P < .0001) and 6717 ± 1183 pg/mL (P < .0001), respectively (Figure 2A), suggesting that IR injury mimicked other NET-related disease cytokine release, and similar TLR7/8/9 mediated pathways may have also been involved.…”
Section: Tnfα Productionmentioning
confidence: 69%
“…Beyond their antimicrobial function (56), it is also important to understand the potential immunomodulatory role of NETs. We previously reported that macrophages are capable of internalizing NETs in a "silent" manner [i.e., without a proinflammatory response (14)], whereas others have found that NETs generated after neutrophil activation by Leishmania promastigotes interfered with IL-4/GM-CSF-driven differentiation of monocytes, resulting in reprogramming into anti-inflammatory macrophages (57). In contrast, previous work has shown that NETs trigger proinflammatory IL-1b secretion in macrophages primed with LPS, and this was enhanced in macrophages from patients with SLE (26,58).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that neutrophil elastase (NE), which was found to be inhibited by α BC, may contribute to the reduced secretion of IL‐12p40 by DCs. NE has been shown to reduce IL‐12 production by macrophages, and it is possible that a similar process may occur in mature DCs.…”
Section: Discussionmentioning
confidence: 99%